Exploiting the waste heat in graphene-based thermionic energy converter by means of thermophotovoltaic cell. (December 2020) - Liao, Tianjun; Lin, Jian; Tao, Chuanyi; Lin, Bihong
Abstract: A coupled system comprising of a graphene-based thermionic energy converter (GTEC) and a thermophotovoltaic cell (TPVC) is proposed to recover the waste heat from the anode of GTEC for additional power generation. Based on energy balance principle, the operating temperature of the anode is numerically calculated. Neglecting the non-ideal factors, the local maximum power density 4.46 W cm −2 and efficiency 0.573 of the system are determined for given related parameters. An overall maximum efficiency 0.584 is obtained by optimizing the cathode's temperature, while local maximum power density is increased with increase of the cathode's temperature. The comparisons between the present work and the previous works are made. The present work demonstrates that the proposed system can achieve higher performances than those of the single GTEC and TPVC operating at the same temperature differences. The effects of the thermal loss at the anode and the non-radiative recombination losses of the PV cell on the system's performances are discussed. The local maximum power density 2.06 W cm −2 and efficiency 0.251 are obtained. An overall maximum efficiency 0.307 can be achieved by optimizing the cathode's work function. The present coupled system is very promising for renewable energy utilization. Highlights: A graphene thermionic power device-thermophotovoltaic cell hybrid system is proposed. The performances of the system are improved by comparing to the previous works. The influences of the non-ideal factors on the system's performances are revealed. The power density 2.06 W cm −2 and efficiency 0.251 of non-ideal system are obtained. The proposed coupled system is helpful for the utilization of renewable energy.